Isolated ventricular septal defect in adults. Clinical and haemodynamic findings. - Otterstad, J E (1983)
Clinical and haemodynamic findings were reviewed in 109 consecutive patients in whom an isolated ventricular septal defect was diagnosed after the age of 15 years (range 15-65 years). Most patients had no or minor cardiac symptoms. Based on the left to right shunt size and pulmonary pressure, 32 (29%) patients had large and 75 (69%) small ventricular septal defects, whereas in two (2%) patients data were insufficiently complete for determining the size. The anatomical location was membranous in 92% and muscular in 8% of the 51 patients in whom this could be assessed from a left ventricular angiogram or the surgeon's report of a subsequent operation, or both. Nine (8%) patients had developed the Eisenmenger syndrome, 12 had aortic regurgitation, and 16 (15%) had bacterial endocarditis, the incidence of the latter being 5.7 per 1000 patient years. Of the 34 (31%) patients who underwent surgery, five (15%) died while in hospital. In contrast with reports from paediatric series our study in adults showed a predominance of small ventricular septal defects and a high frequency of irreversible pulmonary hypertension and serious complications, such as aortic regurgitation and bacterial endocarditis. Thus ventricular septal defects in adults should--regardless of symptoms--be looked on as potentially serious.